The more-than-human biopolitics of swarming – complexity, emergence, and control in military robotics - Hälterlein, Jens (European Journal of International Security)

Fairness - Hambach, Dennis; Settnieri, Julia (Leistungsmessung, Evaluation und Feedback im Fremdsprachenunterricht - Ein Handbuch für Studium, Refendariat und Unterricht)

Prudence and prevention – empirical evidence - Mayrhofer, Thomas; Schmitz, Hendrik (Economics Letters)

Design Space Exploration for Approximate Circuits via Checkpointing and DNN-Based Estimators - Awais, Muhammad; Mohammadi, Hassan Ghasemzadeh; Platzner, Marco (IEEE Transactions on Very Large Scale Integration (VLSI) Systems)

A Two-Stage Approximation Methodology for Efficient DNN Hardware Implementation - Hadipour, Amir Hossein; Jafari, Atousa; Awais, Muhammad; Platzner, Marco (2025 IEEE 28th International Symposium on Design and Diagnostics of Electronic Circuits and Systems (DDECS))

Development of a digital twin for data-driven modeling of punch-bending processes using a graphical modeling notation - Peters, Henning; Mazur, Andreas; Pandey, Ankit Kumar; Trächtler, Ansgar; Hammer, Barbara; Homberg, Werner (at - Automatisierungstechnik)
Abstract In punch-bending, products such as brackets, electronic contacts or spring elements are produced from wire-shaped semi-finished products using separation processes and several successive forming processes. Within the multi-stage straightening and bending processes, cross-stage and quantity-dependent effects have a significant influence on the quality of the end product. In order to optimize the punch-bending process with regard to the resulting component deviations and waste rate, this article presents the concept of a digital twin for an innovative hybrid model of a multi-stage punch-bending process. To ensure efficient development and implementation of the digital twin, the graphical modeling notation DSL4DPiFS is used for additional support. It makes it possible to derive the required interfaces of the Asset Administration Shell of the hybrid data-driven model.

Integration of a digital twin for data-driven modeling of punch-bending processes using the asset administration shell - Peters, Henning; Mazur, Andreas; Trächtler, Ansgar; Hammer, Barbara (Materials Research Proceedings)
Abstract. Within the punch-bending process semi-finished products of strip or wire material are formed and punched in several subsequent steps into a finished product like brackets, mounts, contacts or spring elements. In the context of those multi-stage straightening and bending processes, cross-stage and quantity-dependent effects significantly leads to undesired component deviations. To optimize the punch-bending process with regard to these component deviations and thus the waste rate, the concept of a hybrid data-driven model is presented. To automatically acquire and process this hybrid data while also enable the usage by multiple clients, a digital twin has to be developed. In this paper the communication infrastructure between the punch-bending system and the digital twin is presented, using the Asset Administration Shell as specification. This automated communication is validated using exemplary data from the punch-bending system.

DSL4DPiFS – a graphical notation to model data pipeline deployment in forming systems - Vogel-Heuser, Birgit; Zhang, Mingxi; Krüger, Marius; Vicaria, Alejandra; Gardill, Markus; Jiang, Yuyao; Trächtler, Ansgar; Peters, Henning; Liewald, Mathias; Schenek, Adrian; Heinzelmann, Pascal; Weyrich, Michael (at - Automatisierungstechnik)
Abstract Data-driven methods are increasingly utilized in metal forming processes for monitoring and quality optimization. An adapted modeling notation DSL4DPiFS for forming processes is presented to model hardware, software, and data flow aspects to support the design and analysis of data-driven methods. DSL4DPiFS enables metal forming and automation experts to model field-level information as data sources, and the data sinks for data analysis. The notation was adapted to the requirements of selected metal forming processes and evaluated in three case studies.

Studying the Generalization Behavior of Surrogate Models for Punch-Bending by Generating Plausible Counterfactuals - Mazur, Andreas; Peters, Henning; Artelt, André; Koller, Lukas; Hartmann, Christoph; Trächtler, Ansgar; Hammer, Barbara (Lecture Notes in Computer Science)

Advanced thermomechanical flow forming: A novel approach to α’-martensite control for enhanced material properties - Arian, Bahman; Homberg, Werner; Kersting, Lukas; Trächtler, Ansgar; Rozo Vasquez, Julian; Walther, Frank (Materials Research Proceedings)
Abstract. Flow forming is recognized for its precision in producing rotationally symmetric components, but the use of metastable austenitic stainless steel (AISI 304L) introduces challenges due to uncontrolled strain-induced α’ martensite formation. Variations in factors such as eccentricity and batch inconsistencies lead to unpredictable microstructural profiles, limiting reproducibility [1,2]. This study addresses these issues by incorporating thermal actuators for cryogenic cooling and induction heating to regulate forming temperatures, enabling control of the α’-martensite content. Experimental investigations demonstrate that local tempering during thermomechanical reverse flow forming produces discernible variations in microstructure, affecting mechanical and magnetic properties [3]. Controlled local adjustments of α’-martensite content allow for customization of properties in seamless tubes, advancing manufacturing capabilities for complex, defect-free components. The results presented demonstrate promising strategies for implementation within the context of closed-loop property control in flow forming.
Keywords: Flow Forming; Thermomechanical Forming; α’-Martensite; Property Control

Magneto-optical Kerr effect analysis of strain-induced martensite formation during flow forming of metastable austenitic steel AISI 304L - Rozo Vasquez, Julian; Tappe, Jan; Arian, Bahman; Kersting, Lukas; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (Practical Metallography)
Abstract This paper presents a characterization of the microstructural evolution and its correlation with the magnetic structure due to flow forming of semi-finished tubes of austenitic stainless steel AISI 304L. The plastic deformation triggers a phase transformation of the metastable austenite into α’-martensite. Depending on the combination of production parameters, different fractions of strain-induced α’-martensite were measured by means non-destructive micromagnetic techniques and correlated with the evolution of hardness and the microstructure using electron backscatter diffraction analyses. The magneto-optical Kerr effect analysis was used as a tool to perform a qualitative analysis of the evolution of the magnetic domain structure correlated with the formation of α’-martensite. An analysis of these data allowed to derive surface magnetization hysteresis loops that were compared with integral hysteresis loops of the specimens. It was proven by both methods that the formation of martensite increases the magnetic energy and the spontaneous magnetization of the specimens. The results of this investigation contribute to a better understanding of micromagnetic sensors to monitor and control the formation of α’-martensite in a flow forming. Furthermore, various techniques have demonstrated the evolution of the magnetic properties of the material, which can be applied in applications for invisible coding of workpieces.

Real-time modelling of incremental multi-pass flow forming by a hybrid, data-based model - Kersting, Lukas; Gunasagran, Sharin Kumar; Arian, Bahman; Rozo Vaszquez, Julian; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (Materials Research Proceedings)
Abstract. The incremental flow forming process features a large number of process parameter combinations that can be varied from pass to pass or during a pass. In the future however, a more efficient utilization of this large number of process parameter combinations and a compensation of process disturbances could be required. This is due to a rising demand for increasing the part complexity, e.g. by graded property structures or a more complex geometry. In this context, innovative approaches like closed-loop property control and optimal control are advantageous, but require fast process models of flow forming that are not state of the art. This paper thus proposes a new modelling approach of multi-pass flow forming especially taking the transfer behavior between process parameters and wall thickness evolution from pass to pass into focus. A hybrid modelling approach is developed that combines knowledge about the incremental process character with empirical data regression to a basic analytic relation. The basic relation is further extended by a multi-layer neural network to enhance the overall model accuracy. This hybrid modelling approach is finally validated using experimental data. Thus, it is shown that a suitable model structure was found in context of a future closed-loop control or optimal control for multi-pass flow forming.

Modellbasierter Entwurf und Validierung einer Eigenschaftsregelung für das Drückwalzen metastabiler Austenite - Kersting, Lukas; Arian, Bahman; Rozo Vasquez, Julian; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (at - Automatisierungstechnik)
Zusammenfassung Die Eigenschaftsregelung mit einer online-Messung der Bauteileigenschaften ist ein in der Umformtechnik viel diskutiertes, aber kaum validiertes Konzept, um den Automatisierungsgrad bei der Bauteilfertigung weiter zu erhöhen. Dieser Artikel soll helfen, die Lücke beispielhaft für den Fertigungsprozess des Drückwalzens metastabiler Austenite zu schließen. Der metastabile austenitische Edelstahl ändert hierbei während der Verformung seinen α′-Martensitgehalt und damit verbunden die magnetischen Eigenschaften. Deshalb soll über die Regelung das definierte Einstellen des α′-Martensitgehaltes möglich werden. Im Rahmen des vorliegenden Artikels wird gezeigt, wie mittels des modellbasierten Entwurfs die Eigenschaftsregelung ausgelegt und parametriert werden kann. Zudem beinhaltet der Artikel experimentelle Validierungsergebnisse der zuvor entworfenen Eigenschaftsregelung.

State-space modelling approach for control and observer design in property-controlled reverse flow forming - Kersting, Lukas; Arian, Bahman; Rozo Vasquez, Julian; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (IFAC-PapersOnLine)

Mathematik mit Kindern ausgehend von Spiel- und Routinesituationen in der Kindertagesstätte erkunden? - Bruns, Julia; Mette, Tessa (Frühe Bildung)
Zusammenfassung: Frühe mathematische Bildung, die ihren Ausgangspunkt in den (Spiel-)Situationen der Kindertagesstätte nimmt, kann breite mathematische Erfahrungen ermöglichen, wenn die (Spiel-)Situationen entsprechende Möglichkeiten bieten. Erste Studien weisen darauf hin, dass in diesen Situationen verschiedene mathematische Inhalte angesprochen werden können. Allerdings konzentrieren sich bisherige Studien auf ausgewählte Kontexte oder Inhaltsbereiche. Diese Studie zielt daher auf eine vertiefte Analyse der Gelegenheiten für mathematische Erfahrungen, die in verschiedenen (Spiel-)Situationen im Alltag der Kindertagesstätte entstehen können. Dazu wurde eine videobasierte Beobachtungsstudie mittels einer Action-Kamera in einer Kindertagesstätte durchgeführt. Die Ergebnisse zeigen, dass eine Vielfalt von mathematischen Inhalten in (Spiel-)Situationen in der Kindertagesstätte beobachtet werden kann, einzelne Inhalte jedoch nur in formellen Lernsituationen auftreten.

Beethovens Eigenbearbeitungen und digitale Heuristik. Erkundungen mit den synoptischen Doppeleditionen und Analysewerkzeugen des Projekts Beethovens Werkstatt - Münzmay, Andreas

Submatrix and GPU-accelerated implementation of density matrix tight-binding - Katbashev, Abylay; Schade, Robert; Laß, Michael; Müller, Marcel; Grimme, Stefan; Hansen, Andreas; Kühne, Thomas (The Journal of Chemical Physics)
Effective single-particle theories, such as Hartree–Fock, density functional theory, and tight-binding, are limited by the computational cost of the self-consistent field (SCF) procedure, which typically scales cubically with the system size. This makes large-scale applications impractical without specialized algorithms and hardware. Here, we present the submatrix and graphical processing unit (GPU)-accelerated software implementation of the PTB tight-binding potential, realized in the open-source ptb codebase [M. Mueller, A. Katbashev, and S. Ehlert (2025). “grimme-lab/ptb: v3.8.1,” Zenodo. https://zenodo.org/records/17015872]. We first benchmark a traditional diagonalization-based SCF solver against density-matrix-based purification approaches, systematically varying both system size and computer hardware. Our findings show that the usage of GPUs permits shifting the boundaries to much larger systems than previously thought feasible, achieving an overall 10–15-fold performance speedup. Second, we introduce the implementation of a decomposition-type submatrix method, specifically designed for efficient operation on mid- to large-sized systems, to address the computational overhead associated with full-system diagonalization. We demonstrate that, from a certain dimension (≈104 basis functions) on, our submatrix method reduces the overall computational cost while maintaining acceptable numerical accuracy. Our study demonstrates the significance of the interplay between modern hardware, algorithmic considerations, and novel tight-binding methods, paving the way for further development in this direction.

Gratis - Köstliches zwischen den Jahren (Hebr 13,8-9b) 31.12.2025 Silvester/Altjahrsabend - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Analyse akademischer Selbstkonzepte gewerblich-technischer Lehramtsstudierender unter besonderer Beachtung soziodemographischer Heterogenität und Vergleichsprozessen als Entwicklungseinflüsse - Vernholz, Mats
Selbstkonzepte werden als mentale Repräsentationen einer Person von sich selbst definiert und stehen aufgrund ihrer Bedeutung für den Berufserfolg von (angehenden) Lehrkräften im Fokus der Forschung zur Professionalisierung von Lehrkräften. Ziel der vorliegenden Arbeit ist die de-taillierte Betrachtung der Ausprägungen akademischer Selbstkonzepte von gewerblich-techni-schen Lehramtsstudierenden im Master of Education zur Analyse der Struktur, Entwicklungsein-flüsse und Beziehungen zwischen verschiedenen Dimensionen akademischer Selbstkonzepte anhand eines sequentiellen Mixed-Methods-Designs. Dieses besteht aus einer quantitativen Studie (n=115), angelehnt an das TPACK-Modell, und einer anschließenden qualitativen Inter-viewstudie (n=18) angelehnt an das PCK-Modell. Es zeigt sich, dass akademische Selbstkonzepte angehender Lehrkräfte anhand von Professionswissensmodellen strukturierbar sind. Dies trifft sowohl auf die Strukturierung anhand des TPACK-Modells als auch anhand des PCK-Modells zu. Als Entwicklungseinflüsse zeigen sich besonders Aspekte: praktische Erfahrungen im schulischen sowie im fachwissenschaftlichen Bereich und auch die Auswirkungen sozialer und dimensionaler Vergleichsprozesse. Bei den Auswirkungen von Vergleichsprozessen fungiert jedoch die wahr-genommene Relevanz der jeweiligen Dimensionen der akademischen Selbstkonzepte als Mode-rator. Abschließend werden forschungsmethodische sowie hochschulbildungspraktische Im-plikationen der Ergebnisse diskutiert.

Modular Energy Demand Modeling of Manufacturing Processes for Energy Efficiency Improvement - Naumann, Marius; Henne, Kevin; Ostermann, Moritz; Schlosser, Florian; Meschede, Henning (Procedia CIRP)